Depression Symptoms Mediate Mismatch Between Perceived Severity of the COVID-19 Pandemic and Preventive Motives - Park, Jiwon; Lee, Seungmin; Sul, Sunhae; Chung, Dongil (Frontiers in Psychology, 2021)
The present study monitored changes in beliefs about the COVID-19 pandemic, depressive symptoms, and preventive motives between the first wave and the second wave in South Korea using an online survey administered to 1144 individuals nationally representative for age, gender, and areas of residence. While participants correctly updated their beliefs about the worsening pandemic situations, perceived importance of social distancing did not change, and their motives to follow prevention measures shifted toward compulsory rather than voluntary motives. This inconsistency appeared to be mediated by depressive symptoms, such that negative belief changes followed by increased depressive symptoms were associated with decreased perceived importance of social distancing and decreased voluntary motives. Our data highlights the importance of psychological responses to the dynamically evolving pandemic situations in promoting preventive behaviors.